Cationic ion supplementing material and preparation method thereof, electrolyte, positive pole piece, diaphragm, battery and electric device
By using a cladding-coated cationic material in lithium-ion batteries, the release of compounds is controlled, and the problem of cation loss during the battery cycle is solved, the battery cycle performance and Coulomb efficiency are improved, while the cost is reduced.
Patent Information
- Application Number
- CN202311352386.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-18
- Publication Date
- 2025-04-18
AI Technical Summary
Lithium-ion batteries experience cation loss during circulation, resulting in a degradation in the battery's circulation performance.
A cationic supplement material is used, which includes a compound containing a cationic element and a cladding layer. By covering the cladding layer on the surface of the core material, the compound is controlled to reduce release in the early stage of the cycle, and then gradually release it into the electrolyte later in the cycle to supplement the cation.
It effectively improves the battery's circulation performance and Coulomb efficiency, extends the battery's service life, and reduces the cost of lithium salt.
Smart Images

Figure CN119852560A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a cation-supplementing material and a preparation method thereof, an electrolyte, a positive electrode sheet, a diaphragm, a battery and an electrical device. Background Art
[0002] With the rapid growth of portable electronic devices and electric vehicles, the demand for power batteries is also growing. Among them, the electrochemical performance of batteries is also attracting more and more attention.
[0003] Due to some irreversible reactions such as the formation of the solid electrolyte membrane (SEI membrane) on the surface of the negative electrode during the initial charge and discharge formation process, the positive electrode material will experience ion loss, which will lead to a decrease in the cycle performance of the battery. Taking lithium-ion batteries as an example, in the prior art, in order to solve the above problem, a lithium supplement is added to the battery to supplement the lithium ions lost during the initial formation process. Summary of the invention
[0004] The main purpose of the present invention is to provide a cation-supplementing material, aiming to improve the cycle performance of the battery.
[0005] To achieve the above object, the present invention proposes a cation-supplementing material, comprising a core material and a coating layer arranged on the surface of the core material, wherein the core material comprises a compound containing a cation-supplementing element.
[0006] Taking into account the phenomenon of cation loss during the battery cycle, the cation loss phenomenon occurs not only in the formation process, but also in the cycle process. In particular, as the cycle proceeds, the cations are continuously consumed. In the middle and late stages of the battery cycle, the lack of cations will lead to a decline in the battery cycle performance.
[0007] In order to solve the above problems, a coating layer is coated on the surface of the compound containing the cation-supplementing element, which helps to reduce the release of the compound containing the cation-supplementing element into the electrolyte during formation or the initial stage of circulation, so that the compound containing the cation-supplementing element is released into the electrolyte in the middle and late stages of circulation, replenishing the cations consumed in the battery and improving the cycle performance of the battery.
[0008] It is understandable that if Figure 1 , which is a schematic structural diagram of a cation-supplementing material, the surface of a core material 10 is coated with a coating layer 20 .
[0009] Optionally, the cation-supplementing material is applied to a lithium-ion battery, and the compound containing the cation-supplementing element includes a non-lithium element compound.
[0010] Of course, the cation-supplementing material of the present application can also be applied to other types of batteries, such as sodium-ion batteries, and those skilled in the art can configure it according to specific needs.
[0011] Considering that lithium salts are often expensive for lithium-ion batteries, which increases the cost of the battery, non-lithium element compounds are used to supplement cations, thereby improving battery cycle performance and reducing costs.
[0012] Optionally, the decomposition potential of the compound containing the cation-complementing element is 2V to 5V, preferably, 3V to 5V.
[0013] The compound containing the cation-supplementing element of the present application is not directly dissolved in the electrolyte, but after being exposed from the coating layer, it is oxidized and decomposed at a certain potential to produce cations, thereby supplementing the cations. For example, during the long-term cycle of the battery, the electrolyte will produce trace acidic substances, which will gradually etch the surface of the micro-coating layer. During use, the compound containing the cation-supplementing element inside the coating layer is gradually exposed, and after contacting with the positive electrode, it is oxidized and decomposed, which can play a role in supplementing cations.
[0014] It can also be understood that when the compound containing the cation-supplementing element is oxidized and decomposed at a certain potential, cations are released and electrons are given, which replenish the cations and electrons of the battery system and improve the long-term cycle performance and coulomb efficiency of the battery. In addition, the supplemented cations also play a role in participating in the film formation of the negative electrode, which helps to repair the film layer on the surface of the negative electrode during the cycle, and the supplemented cations can also play an electrostatic shielding role to inhibit the growth of lithium dendrites.
[0015] The decomposition potential of the compound containing the complementary cation element is 2 V to 5 V, preferably 3 V to 5 V. It is understood that the decomposition potential cannot be too low to reduce the phenomenon that the compound containing the complementary cation element is difficult to decompose at a lower potential.
[0016] Optionally, the compound containing a cation-supplementing element includes at least one of a Group IA element compound and a Group IA element compound.
[0017] It is understandable that information on Group IA elements and Group IIA elements can be obtained from the periodic table. For example, Group IA elements include sodium, potassium, etc., and Group IIA elements include calcium, magnesium, etc.
[0018] Optionally, the Group IA element compound includes at least one of an oxide of a Group IA element, a peroxide of a Group IA element, and an oxalate of a Group IA element;
[0019] And / or, the Group IIA element compound includes at least one of an oxide of a Group IIA element, a peroxide of a Group IIA element, and an oxalate of a Group IIA element.
[0020] It is to be understood that the compounds of Group IA elements include but are not limited to at least one of oxides of Group IA elements, peroxides of Group IA elements, and oxalates of Group IA elements; and / or, the compounds of Group IIA elements include but are not limited to at least one of oxides of Group IIA elements, peroxides of Group IIA elements, and oxalates of Group IIA elements.
[0021] Optionally, the compound containing a cationic supplementing element includes at least one of sodium oxide, sodium peroxide, sodium oxalate, potassium oxide, potassium peroxide, potassium oxalate, magnesium oxide, magnesium peroxide, magnesium oxalate, calcium oxide, calcium peroxide, calcium oxalate, strontium oxide, strontium peroxide and strontium oxalate.
[0022] It will be appreciated that the compounds containing cationic complementary elements include but are not limited to at least one of sodium oxide, sodium peroxide, sodium oxalate, potassium oxide, potassium peroxide, potassium oxalate, magnesium oxide, magnesium peroxide, magnesium oxalate, calcium oxide, calcium peroxide, calcium oxalate, strontium oxide, strontium peroxide and strontium oxalate.
[0023] Optionally, the Dv50 value of the cation-supplementing material is in the range of 50 nm to 150 μm, preferably, 50 nm to 10 μm.
[0024] It is understandable that if the Dv50 of the cation-supplementing material is too small, the coating property of the coating layer is poor and it is difficult to form a coating state; if the Dv50 of the cation-supplementing material is too large, when the cation-supplementing material is set on the positive electrode plate, after the cation-supplementing material is decomposed, larger pores will be left in the positive electrode coating, the mechanical properties of the plate will be reduced, and the positive electrode coating will easily collapse and break. When the cation-supplementing material is prepared into a slurry and applied to the diaphragm, if the Dv50 of the cation-supplementing material is too large, it is difficult to obtain a cation-supplementing material coating of suitable thickness.
[0025] Therefore, taking all factors into consideration, the Dv50 range of the cation-supplementing material is 50 nm to 150 μm, preferably 50 nm to 10 μm.
[0026] Optionally, the Dv50 value of the compound containing a cation-complementing element is in the range of 20 nm to 100 μm, preferably, 50 nm to 2 μm.
[0027] The compound containing the cation-replenishing element is used to be coated in the coating layer. If the Dv50 of the compound containing the cation-replenishing element is too small, the coating layer is difficult to coat on the surface of the compound containing the cation-replenishing element. If the Dv50 of the compound containing the cation-replenishing element is too large, the Dv50 of the prepared cation-replenishing material will be too large. When the cation-replenishing material is set on the positive electrode plate, after the cation-replenishing material is decomposed, larger pores will be left in the positive electrode coating, the mechanical properties of the plate will be reduced, and the positive electrode coating will easily collapse and break. When the cation-replenishing material is prepared into a slurry and applied to the diaphragm, if the Dv50 of the cation-replenishing material is too large, it will be difficult to obtain a cation-replenishing material coating of suitable thickness.
[0028] Therefore, taking all factors into consideration, the Dv50 range of the compound containing a cation-complementing element is 20 nm to 100 μm, preferably, 50 nm to 2 μm.
[0029] Optionally, the ratio of the mass of the compound containing the cation-complementing element to the mass of the coating layer ranges from 1:99 to 99:1, preferably, from 50:50 to 80:20.
[0030] In order to prepare a cation-supplementing material with a good coating state and a coating layer with a suitable thickness, the ratio of the mass of the compound containing the cation-supplementing element to the mass of the coating layer ranges from 1:99 to 99:1, preferably, 50:50 to 80:20.
[0031] Optionally, the coating layer has a thickness ranging from 50 nm to 3 μm, preferably from 100 nm to 500 nm.
[0032] Considering that the wall thickness of the coating layer has an impact on the cation-replenishing material and the cation replenishment in the middle and late stages of the cycle, for example, when the coating layer is at a certain thickness, the longer the period of oxidation and decomposition of the compound containing the cation-replenishing element in the cation-replenishing material, the more continuously the cations can be replenished, and the cycle performance will be improved. However, when the thickness of the coating layer is too thick, the coating layer is difficult to be swollen by the solvent in the electrolyte or etched by the acid, which is not conducive to exposing the compound containing the cation-replenishing element. For example, in the worst case, when the cycle life of the battery reaches the end, the compound containing the cation-replenishing element can achieve cation replenishment, and it is difficult to improve the performance of the battery at this time. For this reason, based on comprehensive considerations, the thickness range of the coating layer is 50nm to 3μm, preferably 100nm to 500nm.
[0033] It can also be understood that the compound containing the cation-complementing element in the present application is solid and insoluble in the electrolyte. The coating layer is used to isolate electrons (to reduce the loss of electrons and oxidative decomposition reaction of the compound containing the cation-complementing element in the coating layer). Therefore, the coating layer does not need to be too thick.
[0034] The compound containing the cation-replenishing element in the present application is in a solid state, and the solid state has mechanical strength compared to the liquid state. During the extrusion process of the positive electrode plate and the diaphragm, the cation-replenishing material is not easy to be crushed or broken, and it is difficult for the coating layer of the cation-replenishing material to be damaged due to the extrusion process during the preparation process, thereby reducing the direct release of the compound containing the cation-replenishing element in the coating layer, thereby improving the subsequent cation replenishment in the battery cycle.
[0035] Optionally, the material of the coating layer includes at least one of gelatin-modified amino resin, polyurea resin, and polyvinyl chloride.
[0036] Gelatin is a peptide molecule polymer substance and a multi-level hydrolysis product of collagen with the molecular formula AlH3KO8S2.
[0037] Amino resin is a general term for resins formed by condensation of amino-containing compounds and formaldehyde.
[0038] Polyurea resins are a class of compounds formed by the reaction of isocyanate components with amino compounds.
[0039] Polyvinyl chloride is a thermoplastic resin formed by the polymerization of vinyl chloride under the action of an initiator.
[0040] It is understood that the material of the coating layer includes but is not limited to at least one of gelatin-modified amino resin, polyurea resin, and polyvinyl chloride. For example, gelatin-modified amino resin is used as the capsule wall, wherein gelatin has good coating and etching properties, and the addition of amino resin can enhance the mechanical properties of gelatin, so the two form a composite capsule wall, improving the functionality and mechanical properties of the capsule wall.
[0041] The coating layer is used to slow down the release rate of the compound containing the cation-supplementing element inside the coating layer. Specifically, in the early cycle of the battery, due to the coating effect of the coating layer, the compound containing the cation-supplementing element inside is difficult to be oxidized and decomposed to replenish the cation. In the long-term cycle process, the electrolyte will produce trace acidic substances, which will gradually etch the surface of the coating layer (for example, gelatin-modified amino resin), and then the compound containing the cation-supplementing element inside the coating layer will gradually be exposed, and after contacting with the positive electrode, it will be oxidized and decomposed, which can play a good role in long-term cycle cation replenishment.
[0042] It can also be understood that, in addition to being etched by the acidic substances in the electrolyte, the coating layer can also utilize the coating layer material (such as polyurea resin) to swell under long-term immersion in the electrolyte to form a porous structure. The compounds containing cation-supplementing elements in the coating layer are gradually exposed from the porous positions, and after contacting with the positive electrode, they are oxidized and decomposed, which can play a good role in long-term cyclic cation replenishment.
[0043] Optionally, the coating layer completely covers the surface of the core material.
[0044] Full coating means that the coating layer is continuously coated on the surface of the core material, and the surface of the core material is not exposed.
[0045] In order to reduce the exposure of the core material to oxidation and decomposition during the formation process, it is preferred that the coating layer completely covers the surface of the core material. In this way, the coating layer is etched by the acidic substances (such as HF) generated during the battery cycle, and the core material is slowly exposed, which helps to replenish cations in the middle and late stages of the cycle.
[0046] Optionally, the present application also provides an electrolyte, which includes the cation-supplementing material as described.
[0047] By directly adding the cation-replenishing material into the electrolyte, the compounds containing the cation-replenishing elements in the coating layer can be slowly exposed during the battery cycle, so that the compounds containing the cation-replenishing elements are oxidized and decomposed after contacting the positive electrode, which can play a good role in long-term cyclic cation replenishment.
[0048] Optionally, the mass percentage of the cation-supplementing material to the total mass of the electrolyte is in the range of 5% to 20%, preferably, 10% to 12%.
[0049] Considering that if the mass of the cation-replenishing material inside the battery is insufficient, it will be difficult to sufficiently replenish cations in the middle and late stages of the battery cycle. At the same time, if the mass of the cation-replenishing material inside the battery is too much, there will be excessive cation replenishment, making it difficult to further improve the cycle performance, and at the same time, the mass energy density of the battery will be reduced. For this reason, when the cation-replenishing material is directly added to the electrolyte, the mass percentage of the cation-replenishing material to the total mass of the electrolyte is in the range of 5% to 20%, preferably 10% to 12%.
[0050] Optionally, the present application also provides a positive electrode plate, wherein the positive electrode plate comprises the cation-supplementing material as described.
[0051] It is understandable that the cation-supplementing material can be added inside the positive electrode coating or disposed on the surface of the positive electrode coating.
[0052] Optionally, the positive electrode plate includes a current collector and a positive electrode coating disposed on the current collector, and the mass percentage of the cation-supplementing material to the total mass of the positive electrode coating ranges from 0.1% to 20%, preferably, from 0.5% to 5%.
[0053] On the one hand, if the mass of the cation-replenishing material inside the battery is insufficient, it will be difficult to sufficiently replenish cations in the middle and late stages of the battery cycle. At the same time, if the mass of the cation-replenishing material inside the battery is too much, there will be excessive cation replenishment, making it difficult to further improve the cycle performance, and at the same time reducing the mass energy density of the battery.
[0054] On the other hand, considering that the compounds containing cation-supplementing elements will decompose and be consumed during the cycle, thereby leaving pores in the positive electrode coating, if too much cation-supplementing material is added to the positive electrode coating, the porosity of the positive electrode coating will increase in the later stage of the cycle. If the porosity is too high, although the wettability of the positive electrode coating to the electrolyte can be improved, the mechanical strength of the positive electrode coating will decrease, and the positive electrode coating will be prone to collapse and rupture. Therefore, taking all factors into consideration, the mass percentage of the cation-supplementing material to the total mass of the positive electrode coating is in the range of 0.1% to 20%, preferably 0.5% to 5%.
[0055] Optionally, the positive electrode plate includes at least two layers of coating, at least one of the coatings is arranged on the current collector, and at least another coating is arranged on the side of at least one of the coatings away from the current collector, and the mass percentage of the mass of the cation-replenishing material in at least one of the coatings is defined as W1, and the mass percentage of the mass of the cation-replenishing material in at least another of the coatings is defined as W2, satisfying that W2 is greater than W1.
[0056] It is understandable that in order to facilitate the damage of the coating layer and effectively oxidize and decompose the compound containing the cation-supplementing element inside the coating layer, the coating layer needs to contact the electrolyte. When the cation-supplementing material is added to the positive electrode coating, the probability of contacting the electrolyte is different at different positions of the coating.
[0057] In order to facilitate the contact of cation-supplementing materials with the electrolyte, Figure 2 As shown, the positive electrode plate 100 includes at least two layers of coating, at least one coating 102 is arranged on the current collector 101, and at least another coating 103 is arranged on the side of the at least one coating 102 away from the current collector 101, so that the at least another coating 103 is closer to the surface of the positive electrode coating, increasing the probability of contact with the electrolyte; and it is defined that the mass percentage of the cation-replenishing material in the at least one coating 102 to the mass percentage of the at least one coating 102 is W1, and the mass percentage of the cation-replenishing material in the at least another coating 103 to the mass percentage of the at least another coating 103 is W2, satisfying that W2 is greater than W1, that is, the mass percentage of the cation-replenishing material in the at least two layers of coating is distributed in a concentration gradient; at this time, the mass percentage of the cation-replenishing material in the at least another coating 103 is greater than the mass percentage of the cation-replenishing material in the at least one coating 102, which helps the cation-replenishing material in the at least another coating 103 to contact the electrolyte.
[0058] At the same time, after the cation-replenishing material is decomposed, it helps to improve the porosity of the at least another coating 103. The improvement of the porosity of the at least another coating 103 can further improve the wetting of the positive electrode coating with the electrolyte, so that the electrolyte can penetrate into the at least one coating 102, thereby improving the contact of the cation-replenishing material in the at least one coating 102 with the electrolyte, and improving the decomposition of the cation-replenishing material in the at least one coating 102. In addition, the cation-replenishing material in the at least two layers of coating is distributed in a gradient, which can extend the period of slow release of the cation-replenishing material and improve the battery cycle performance.
[0059] Optionally, the positive electrode plate includes a positive electrode material, and the positive electrode material includes one or more of lithium iron phosphate, a ternary layered material, and a spinel positive electrode material.
[0060] The positive electrode plate of the present application includes but is not limited to positive electrode materials, and the positive electrode materials include one or more of lithium iron phosphate, ternary layered materials, and spinel positive electrode materials.
[0061] Optionally, the present application also provides a membrane, which includes the cation-supplementing material as described.
[0062] Optionally, the diaphragm includes a first diaphragm layer and a second diaphragm layer, the second diaphragm layer includes the cation-supplementing material, the diaphragm is arranged on one side of the positive electrode sheet or the negative electrode sheet, and the second diaphragm layer is facing the side of the positive electrode sheet.
[0063] like Figure 3 As shown, a diaphragm 200 of an embodiment of the present application includes a first diaphragm layer 201 and a second diaphragm layer 202. Considering that the decomposition of compounds containing cation-supplementing elements requires a certain decomposition potential, and the potential of the positive electrode is high, which is conducive to decomposition, therefore, the second diaphragm layer 202 including cation-supplementing material is used to face the side of the positive electrode plate.
[0064] Optionally, the mass percentage of the cation-compensating material to the mass of the separator is 5% to 200%, preferably 50% to 80%.
[0065] Considering that if the mass of the cation-replenishing material inside the battery is insufficient, it is difficult to fully replenish cations in the middle and late stages of the battery cycle. At the same time, if the mass of the cation-replenishing material inside the battery is too much, the cations will be excessively replenished, making it difficult to further improve the cycle performance, and the mass energy density of the battery will also be reduced. Taking all factors into consideration, the mass percentage of the mass of the cation-replenishing material to the mass of the diaphragm is 5% to 200%, preferably 50% to 80%.
[0066] Optionally, the second diaphragm layer has a thickness ranging from 50 nm to 50 μm, preferably from 2 μm to 5 μm.
[0067] Considering that the diaphragm needs to have a certain degree of air permeability to facilitate ion transmission, and the thickness of the diaphragm cannot be too large to reduce the thickness of the entire battery cell, after the battery cell is installed in the battery cell shell, it helps the battery cell have sufficient expansion space in the battery cell shell.
[0068] That is, if the thickness of the second diaphragm layer is too thick, the air permeability of the entire diaphragm will be reduced, affecting the penetration of the electrolyte into the diaphragm and the migration of ions between the diaphragms. At the same time, if the thickness of the second diaphragm layer is too thick, it will also occupy the volume of the battery cell and reduce the energy density. If the thickness of the second diaphragm layer is too thin, the quality of the cation-supplementing material will be reduced, which is not conducive to the subsequent replenishment of cations in the cycle.
[0069] Based on the above considerations, the thickness of the second diaphragm layer ranges from 50 nm to 50 μm, preferably from 2 μm to 5 μm.
[0070] Optionally, the material of the diaphragm includes one or more of polyethylene or polypropylene.
[0071] The material of the diaphragm of the present application includes but is not limited to one or more of polyethylene or polypropylene.
[0072] Optionally, the present application also provides a method for preparing a cation-supplementing material, comprising:
[0073] preparing a prepolymer emulsion for a coating layer;
[0074] The compound containing the cation-compensating element is added into the prepolymer emulsion of the coating layer, stirred and heated to obtain the cation-compensating material.
[0075] Prepolymer is a substance formed by preliminary polymerization of monomers.
[0076] Prepolymer emulsion, the state in which the prepolymer is dispersed in water to form an emulsion.
[0077] In order to prepare the cation-supplementing material in which the compound containing the cation-supplementing element is coated in the coating layer, a prepolymer emulsion of the coating layer can be prepared, and the compound containing the cation-supplementing element is added to the prepolymer emulsion of the coating layer, and stirred and heated to obtain the cation-supplementing material. That is, the compound containing the cation-supplementing element is added to the prepolymer emulsion of the coating layer, and the prepolymer is further polymerized on the surface of the compound containing the cation-supplementing element to obtain the compound containing the cation-supplementing element coated in the coating layer.
[0078] Optionally, the step of preparing the prepolymer emulsion of the coating layer includes: mixing the constituent monomers of the coating layer with a solvent, and heating the mixture to obtain the prepolymer emulsion of the coating layer.
[0079] Optionally, the step of mixing the monomers constituting the coating layer with a solvent and heating to obtain a prepolymer emulsion of the coating layer includes: mixing the monomers constituting the coating layer, which are amino resin monomers, formaldehyde substances, gelatin and water, to obtain a mixed solution, adjusting the pH value of the obtained mixed solution to 6.0 to 8.5, heating to 40° C. to 70° C., and keeping the temperature for 20 min to 60 min to obtain a prepolymer emulsion of the coating layer;
[0080] The mass of the amino resin monomer is 20% to 70% of the mass of the compound containing the cation-supplementing element; the formaldehyde substance is 15% to 120% of the mass of the amino resin monomer; and the gelatin is 3% to 16% of the mass of the amino resin monomer.
[0081] For example, taking gelatin-modified amino resin as a coating layer, amino resin monomer, formaldehyde, gelatin and water are mixed, the pH value of the obtained mixed solution is adjusted to 6.0 to 8.5, heated to 40°C to 70°C, and kept warm for 20min to 60min to obtain a gelatin-modified amino resin prepolymer solution; an appropriate amount of a compound containing a cation-supplementing element is added to the gelatin-modified amino resin prepolymer solution, the temperature is raised to 40°C to 60°C, and the mixture is stirred thoroughly. The mixture is filtered and vacuum dried at 70°C to obtain a cation-supplementing material.
[0082] Optionally, the step of adding the compound containing the cation-supplementing element to the prepolymer emulsion of the coating layer, stirring and heating to obtain the cation-supplementing material comprises: adding the compound containing the cation-supplementing element to the prepolymer emulsion of the coating layer, stirring, heating to 40° C. to 60° C., filtering, and drying to obtain the cation-supplementing material;
[0083] Wherein, the mass ratio of the compound of the cation-supplementing element to the prepolymer emulsion of the coating layer ranges from 20% to 80%.
[0084] The compound containing the cation-complementing element is added to the prepolymer emulsion of the coating layer, and stirred to fully disperse the compound containing the cation-complementing element and the prepolymer emulsion of the coating layer, thereby improving the dispersibility of the compound containing the cation-complementing element and facilitating the preparation of a cation-complementing material of a suitable size. The prepolymer is heated to 40° C. to 60° C. so that a polymerization reaction occurs on the surface of the compound containing the cation-complementing element, and a coating layer is formed on the surface of the compound containing the cation-complementing element to coat the compound containing the cation-complementing element. The cation-complementing material is obtained by filtering and drying.
[0085] Optionally, the present application also provides a battery, the battery comprising the cation-supplementing material as described;
[0086] Or, comprising the electrolyte as described;
[0087] Or, comprising the positive electrode sheet as described;
[0088] Or, comprising a diaphragm as described;
[0089] Alternatively, the cation-supplementing material comprises the cation-supplementing material obtained by the preparation method of the cation-supplementing material as described above.
[0090] The present application also provides an electrical device, which includes the battery as described above.
[0091] The present application coats a coating layer on the surface of the compound containing the cation-replenishing element, which helps to reduce the release of the compound containing the cation-replenishing element into the electrolyte during formation or the initial stage of circulation, so that the compound containing the cation-replenishing element is released into the electrolyte in the middle and late stages of circulation, replenishing the cations consumed in the battery and improving the cycle performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0092] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0093] Figure 1 is a schematic diagram of a cation-supplementing material according to one embodiment of the present application;
[0094] Figure 2 is a schematic diagram of a positive electrode sheet according to an embodiment of the present application;
[0095] Figure 3 is a schematic diagram of a diaphragm according to an embodiment of the present application;
[0096] Figure 4 This is a schematic flow chart of a method for preparing a cation-supplementing material according to one embodiment of the present application;
[0097] Figure 5 is a schematic diagram of a battery cell according to an embodiment of the present application;
[0098] Figure 6 yes Figure 5 An exploded view of a battery cell according to an embodiment of the present application is shown;
[0099] Figure 7 is a schematic diagram of a battery module according to an embodiment of the present application;
[0100] Figure 8 is a schematic diagram of a battery pack according to an embodiment of the present application;
[0101] Fig. 9 yes Figure 8 An exploded view of a battery pack according to an embodiment of the present application is shown;
[0102] Fig.10 It is a schematic diagram of an electrical device using a battery cell according to an embodiment of the present application as a power source.
[0103] Description of Figure Numbers:
[0104] Label name Label name 1 Battery Pack 5 Battery Cell 2 Upper box 51 case 3 Lower box 52 Electrode assembly 4 Battery Module 53 Cover 10 core material 20 Coating 100 Positive electrode 101 current collector 102 At least one coating 103 At least one other coating 200 Diaphragm 201 First diaphragm layer 202 Second diaphragm layer
[0105] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0106] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0107] Hereinafter, the embodiments of the cation-supplementing material and its preparation method, electrolyte, positive electrode plate, separator, battery and electrical device of the present application are specifically disclosed with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0108] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0109] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0110] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0111] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0112] With the rapid growth of portable electronic devices and electric vehicles, the demand for power batteries is also growing. Among them, the electrochemical performance of batteries is also attracting more and more attention.
[0113] Due to some irreversible reactions such as the formation of the solid electrolyte membrane (SEI membrane) on the surface of the negative electrode during the initial charge and discharge formation process, the positive electrode material will experience ion loss. Taking lithium-ion batteries as an example, in the prior art, in order to solve the above problem, a lithium supplement is added to the battery. The lithium supplement is used to supplement the lithium ions lost during the initial formation process.
[0114] Taking into account the phenomenon of cation loss during the battery cycle, the cation loss phenomenon occurs not only in the formation process, but also in the cycle process. In particular, as the cycle proceeds, the cations are continuously consumed. In the middle and late stages of the battery cycle, the lack of cations will lead to a decline in the battery cycle performance.
[0115] For example, in lithium-ion batteries, as long-term cycling proceeds, the negative electrode SEI film will continuously consume lithium in the system during the charge and discharge process, thereby causing the capacity of the lithium-ion battery to decay, which will lead to a decrease in the battery's cycle performance.
[0116] In order to solve the above problems, the present application proposes a cation-supplementing material, comprising a core material and a coating layer arranged on the surface of the core material, wherein the core material comprises a compound containing a cation-supplementing element.
[0117] The core material and the coating layer arranged on the surface of the core material refer to the core material being located inside the coating layer, such as Figure 1 , which is a schematic structural diagram of a cation-supplementing material, the surface of a core material 10 is coated with a coating layer 20 .
[0118] Coating the coating layer on the surface of the compound containing the cation-supplementing element helps to reduce the release of the compound containing the cation-supplementing element into the electrolyte during formation or the initial stage of circulation, so that the compound containing the cation-supplementing element is released into the electrolyte in the middle and late stages of circulation, replenishing the cations consumed in the battery and improving the cycle performance of the battery.
[0119] It is understandable that the above-mentioned cation-supplementing materials can be applied to lithium-ion batteries or sodium-ion batteries, and can be applied to suitable batteries as needed.
[0120] In one embodiment, the cation-replenishing material is applied to a lithium-ion battery, and the compound containing the cation-replenishing element includes a non-lithium element compound.
[0121] Considering that lithium salts are often expensive for lithium-ion batteries, which increases the cost of the battery, non-lithium element compounds are used to supplement cations, thereby improving battery cycle performance and reducing costs.
[0122] In one embodiment, the decomposition potential of the compound containing the cation-complementing element is 2V to 5V, preferably, 3V to 5V.
[0123] The compound containing the cation-supplementing element of the present application is not directly dissolved in the electrolyte, but after being exposed from the coating layer, it is oxidized and decomposed at a certain potential to produce cations, thereby supplementing the cations. For example, during the long-term cycle of the battery, the electrolyte will produce trace acidic substances, which will gradually etch the surface of the micro-coating layer. During use, the compound containing the cation-supplementing element inside the coating layer is gradually exposed, and after contacting with the positive electrode, it is oxidized and decomposed, which can play a role in supplementing cations.
[0124] It can also be understood that when the compound containing the cation-supplementing element is oxidized and decomposed at a certain potential, cations are released and electrons are given, which replenish the cations and electrons of the battery system and improve the long-term cycle performance and coulomb efficiency of the battery. In addition, the supplemented cations also play a role in participating in the film formation of the negative electrode, which helps to repair the film layer on the surface of the negative electrode during the cycle, and the supplemented cations can also play an electrostatic shielding role to inhibit the growth of lithium dendrites.
[0125] The decomposition potential of the compound containing the complementary cation element is 2 V to 5 V, preferably 3 V to 5 V. It is understood that the decomposition potential cannot be too low to reduce the phenomenon that the compound containing the complementary cation element is difficult to decompose at a lower potential.
[0126] It is understandable that if a compound containing easily decomposable cation-supplementing elements (e.g., potassium salt or sodium salt) is used as a cation supplement for lithium-ion batteries. During the charging process in the early stage of the cycle, when the voltage reaches the decomposition potential of the potassium salt or sodium salt, the potassium salt or sodium salt begins to decompose, and potassium ions enter the electrolyte. However, this process often occurs in the early cycle process. In the late stage of the cycle, since the cation supplementing agent is exhausted, the cation supplementing effect in the late stage of the cycle is not obvious, and the capacity retention performance in the late stage of the cycle cannot be improved.
[0127] In the above 2V to 5V, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 2V, 2.5V, 3V, 3.5V, 4V, 4.5V, 5V, etc., and the range values between any two of the above point values.
[0128] For example, the decomposition potential of potassium oxalate is 4.7V, the decomposition potential of potassium oxide is 3.5V, the decomposition potential of potassium peroxide is 3.2V, the decomposition potential of sodium oxide is 3.6V, the decomposition potential of magnesium oxide is 4.6V, the decomposition potential of magnesium peroxide is 4.5V, the decomposition potential of magnesium oxalate is 4.8V, the decomposition potential of calcium oxide is 4.9V, and the decomposition potential of strontium oxide is 4.8V.
[0129] In one embodiment, the compound containing a cation-supplementing element includes at least one of a Group IA element compound and a Group IIA element compound.
[0130] It is understandable that information on Group IA elements and Group IIA elements can be obtained from the periodic table. For example, Group IA elements include sodium, potassium, etc., and Group IIA elements include calcium, magnesium, etc.
[0131] In one embodiment, the compound of Group IA elements includes at least one of oxides of Group IA elements, peroxides of Group IA elements, and oxalates of Group IA elements; and / or, the compound of Group IIA elements includes at least one of oxides of Group IIA elements, peroxides of Group IIA elements, and oxalates of Group IIA elements.
[0132] It is to be understood that the compounds of Group IA elements include but are not limited to at least one of oxides of Group IA elements, peroxides of Group IA elements, and oxalates of Group IA elements; and / or, the compounds of Group IIA elements include but are not limited to at least one of oxides of Group IIA elements, peroxides of Group IIA elements, and oxalates of Group IIA elements.
[0133] In one embodiment, the compound containing a complementary cationic element includes at least one of sodium oxide, sodium peroxide, sodium oxalate, potassium oxide, potassium peroxide, potassium oxalate, magnesium oxide, magnesium peroxide, magnesium oxalate, calcium oxide, calcium peroxide, calcium oxalate, strontium oxide, strontium peroxide, and strontium oxalate.
[0134] It will be appreciated that the compounds containing cationic complementary elements include but are not limited to at least one of sodium oxide, sodium peroxide, sodium oxalate, potassium oxide, potassium peroxide, potassium oxalate, magnesium oxide, magnesium peroxide, magnesium oxalate, calcium oxide, calcium peroxide, calcium oxalate, strontium oxide, strontium peroxide and strontium oxalate.
[0135] In one embodiment, the Dv50 value of the cation-supplementing material is in the range of 50 nm to 150 μm, preferably, 50 nm to 10 μm.
[0136] Dv50 is the particle size corresponding to when the cumulative particle size distribution percentage of a sample reaches 50%. Its physical meaning is that particles with a particle size larger than it account for 50%, and particles with a particle size smaller than it also account for 50%. Dv50 is also called the median diameter or median particle size. Dv50 is often used to indicate the average particle size of powders.
[0137] Among the sample particles, 50% of the total volume of the particles have a particle size larger than this value, and another 50% of the total volume of the particles have a particle size smaller than this value; Dv50 can represent the median particle size of the sample.
[0138] Dv50 can be tested by methods known in the art. For example, GB / T19077-2016 can be referred to, and a Malvern laser particle size analyzer can be used for characterization testing, such as a Malvern Mastersizer-3000 or other instrument.
[0139] It is understandable that if the Dv50 of the cation-supplementing material is too small, the coating property of the coating layer is poor and it is difficult to form a coating state; if the Dv50 of the cation-supplementing material is too large, when the cation-supplementing material is set on the positive electrode plate, after the cation-supplementing material is decomposed, larger pores will be left in the positive electrode coating, the mechanical properties of the plate will be reduced, and the positive electrode coating will easily collapse and break. When the cation-supplementing material is prepared into a slurry and applied to the diaphragm, if the Dv50 of the cation-supplementing material is too large, it is difficult to obtain a cation-supplementing material coating of suitable thickness.
[0140] Therefore, taking all factors into consideration, the Dv50 range of the cation-supplementing material is 50 nm to 150 μm, preferably 50 nm to 10 μm.
[0141] In the above-mentioned 50nm to 150μm, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 50nm, 80nm, 100nm, 300nm, 500nm, 800nm, 1μm, 5μm, 10μm, 50μm, 80μm, 100μm, 120μm, 140μm, 150μm, etc., as well as the range values between any two of the above-mentioned point values.
[0142] In the above-mentioned 50nm to 10μm, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 50nm, 80nm, 100nm, 300nm, 500nm, 800nm, 1μm, 5μm, 10μm, etc., as well as the range values between any two of the above-mentioned point values.
[0143] In one embodiment, the Dv50 value of the compound containing a cation-complementing element is in the range of 20 nm to 100 μm, preferably, 50 nm to 2 μm.
[0144] The compound containing the cation-replenishing element is used to be coated in the coating layer. If the Dv50 of the compound containing the cation-replenishing element is too small, the coating layer is difficult to coat on the surface of the compound containing the cation-replenishing element. If the Dv50 of the compound containing the cation-replenishing element is too large, the Dv50 of the prepared cation-replenishing material will be too large. When the cation-replenishing material is set on the positive electrode plate, after the cation-replenishing material is decomposed, larger pores will be left in the positive electrode coating, the mechanical properties of the plate will be reduced, and the positive electrode coating will easily collapse and break. When the cation-replenishing material is prepared into a slurry and applied to the diaphragm, if the Dv50 of the cation-replenishing material is too large, it will be difficult to obtain a cation-replenishing material coating of suitable thickness.
[0145] Therefore, taking all factors into consideration, the Dv50 range of the compound containing a cation-complementing element is 20 nm to 100 μm, preferably, 50 nm to 2 μm.
[0146] In the above-mentioned 20nm to 100μm, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 20nm, 40nm, 50nm, 80nm, 100nm, 300nm, 500nm, 800nm, 1μm, 5μm, 10μm, 50μm, 80μm, 100μm, etc., as well as the range values between any two of the above-mentioned point values.
[0147] In the above-mentioned 50nm to 2μm, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 20nm, 40nm, 50nm, 80nm, 100nm, 300nm, 500nm, 800nm, 1μm, 2μm, etc., as well as the range values between any two of the above-mentioned point values.
[0148] In one embodiment, the ratio of the mass of the compound containing the cation-complementing element to the mass of the coating layer ranges from 1:99 to 99:1, preferably, from 50:50 to 80:20.
[0149] In order to prepare a cation-supplementing material with a good coating state and a coating layer with a suitable thickness, the ratio of the mass of the compound containing the cation-supplementing element to the mass of the coating layer ranges from 1:99 to 99:1, preferably, 50:50 to 80:20.
[0150] In the above 1:99 to 99:1, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 1:99, 5:95, 10:90, 20:80, 40:60, 50:50, 70:30, 80:20, 90:10, 95:5, 99:1, etc., as well as the range values between any two of the above point values.
[0151] In the above 50:50 to 80:20, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 50:50, 60:40, 70:30, 80:20, etc., and the range values between any two of the above point values.
[0152] In one embodiment, the thickness of the coating layer ranges from 50 nm to 3 μm, preferably from 100 nm to 500 nm.
[0153] Considering that the wall thickness of the coating layer has an impact on the cation-replenishing material and the cation replenishment in the middle and late stages of the cycle, for example, when the coating layer is at a certain thickness, the longer the period of oxidation and decomposition of the compound containing the cation-replenishing element in the cation-replenishing material, the more continuously the cations can be replenished, and the cycle performance will be improved. However, when the thickness of the coating layer is too thick, the coating layer is difficult to be swollen by the solvent in the electrolyte or etched by the acid, which is not conducive to exposing the compound containing the cation-replenishing element. For example, in the worst case, when the cycle life of the battery reaches the end, the compound containing the cation-replenishing element can achieve cation replenishment, and it is difficult to improve the performance of the battery at this time. For this reason, based on comprehensive considerations, the thickness range of the coating layer is 50nm to 3μm, preferably 100nm to 500nm.
[0154] It can also be understood that the compound containing the cation-complementing element in the present application is solid and insoluble in the electrolyte. The coating layer is used to isolate electrons (to reduce the loss of electrons and oxidative decomposition reaction of the compound containing the cation-complementing element in the coating layer). Therefore, the coating layer does not need to be too thick.
[0155] The compound containing the cation-replenishing element in the present application is in a solid state, and the solid state has mechanical strength compared to the liquid state. During the extrusion process of the positive electrode plate and the diaphragm, the cation-replenishing material is not easy to be crushed or broken, and it is difficult for the coating layer of the cation-replenishing material to be damaged due to the extrusion process during the preparation process, thereby reducing the direct release of the compound containing the cation-replenishing element in the coating layer, thereby improving the subsequent cation replenishment in the battery cycle.
[0156] In the above-mentioned 50nm to 3μm, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 50nm, 80nm, 100nm, 300nm, 500nm, 800nm, 1μm, 2μm, 3μm, etc., as well as the range values between any two of the above-mentioned point values.
[0157] In the above 100nm to 500nm, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 100nm, 120nm, 150nm, 180nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, etc., and the range values between any two of the above point values.
[0158] In one embodiment, the material of the coating layer includes at least one of gelatin-modified amino resin, polyurea resin, and polyvinyl chloride.
[0159] Gelatin is a peptide molecule polymer substance and a multi-level hydrolysis product of collagen with the molecular formula AlH3KO8S2.
[0160] Amino resin is a general term for resins formed by condensation of amino-containing compounds and formaldehyde.
[0161] Polyurea resins are a class of compounds formed by the reaction of isocyanate components with amino compounds.
[0162] Polyvinyl chloride is a thermoplastic resin formed by the polymerization of vinyl chloride under the action of an initiator.
[0163] It is understood that the material of the coating layer includes but is not limited to at least one of gelatin-modified amino resin, polyurea resin, and polyvinyl chloride. For example, gelatin-modified amino resin is used as the capsule wall, wherein gelatin has good coating and etching properties, and the addition of amino resin can enhance the mechanical properties of gelatin, so the two form a composite capsule wall, improving the functionality and mechanical properties of the capsule wall.
[0164] The coating layer is used to slow down the release rate of the compound containing the cation-supplementing element inside the coating layer. Specifically, in the early cycle of the battery, due to the coating effect of the coating layer, the compound containing the cation-supplementing element inside is difficult to be oxidized and decomposed to replenish the cation. In the long-term cycle process, the electrolyte will produce trace acidic substances, which will gradually etch the surface of the coating layer (for example, gelatin-modified amino resin), and then the compound containing the cation-supplementing element inside the coating layer will gradually be exposed, and after contacting with the positive electrode, it will be oxidized and decomposed, which can play a good role in long-term cycle cation replenishment.
[0165] It can also be understood that, in addition to being etched by the acidic substances in the electrolyte, the coating layer can also be swelled by the coating layer material (such as polyurea resin) under long-term immersion in the electrolyte to form a porous structure. The compound containing the cation-supplementing element in the coating layer is gradually exposed from the porous position, and after contacting with the positive electrode, it is oxidized and decomposed, which can play a good role in long-term cyclic cation replenishment.
[0166] In one embodiment, the coating layer completely covers the surface of the core material.
[0167] Full coating means that the coating layer is continuously coated on the surface of the core material, and the surface of the core material is not exposed.
[0168] In order to reduce the exposure of the core material to oxidation and decomposition during the formation process, it is preferred that the coating layer completely covers the surface of the core material. In this way, the coating layer is etched by the acidic substances (such as HF) generated during the battery cycle, and the core material is slowly exposed, which helps to replenish cations in the middle and late stages of the cycle.
[0169] In one embodiment, the present application further provides an electrolyte, which includes the cation-supplementing material as described above.
[0170] By directly adding the cation-replenishing material into the electrolyte, the compounds containing the cation-replenishing elements in the coating layer can be slowly exposed during the battery cycle, so that the compounds containing the cation-replenishing elements are oxidized and decomposed after contacting the positive electrode, which can play a good role in long-term cyclic cation replenishment.
[0171] In one embodiment, the mass percentage of the cation-supplementing material to the total mass of the electrolyte is in the range of 5% to 20%, preferably, 10% to 12%.
[0172] Considering that if the mass of the cation-replenishing material inside the battery is insufficient, it is difficult to fully replenish cations in the middle and late stages of the battery cycle. At the same time, if the mass of the cation-replenishing material inside the battery is too much, the cations will be excessively replenished, making it difficult to further improve the cycle performance, and the mass energy density of the battery will also be reduced. Therefore, when the cation-replenishing material is directly added to the electrolyte, the mass percentage of the mass of the cation-replenishing material to the total mass of the electrolyte is in the range of 5% to 20%, preferably 10% to 12%. For example, the mass of the cation-replenishing material not added to the electrolyte is defined as m1, and the mass of the cation-replenishing material added to the electrolyte is defined as m2. The mass percentage of the mass of the cation-replenishing material to the total mass of the electrolyte is calculated as m2 / (m1+m2)×100%.
[0173] In the above 5% to 20%, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 5%, 6%, 8%, 10%, 12%, 15%, 16%, 18%, 20%, etc., and the range values between any two of the above point values.
[0174] In the above 10% to 12%, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 10%, 10.5%, 11%, 11.5%, 12%, etc., and the range values between any two of the above point values.
[0175] In one embodiment, the present application further provides a positive electrode plate, which includes the cation-supplementing material as described above.
[0176] It is understandable that the cation-supplementing material can be added inside the positive electrode coating or disposed on the surface of the positive electrode coating.
[0177] In one embodiment, the positive electrode plate includes a current collector and a positive electrode coating disposed on the current collector, and the mass percentage of the cation-supplementing material to the total mass of the positive electrode coating ranges from 0.1% to 20%, preferably, from 0.5% to 5%.
[0178] On the one hand, if the mass of the cation-replenishing material inside the battery is insufficient, it will be difficult to sufficiently replenish cations in the middle and late stages of the battery cycle. At the same time, if the mass of the cation-replenishing material inside the battery is too much, there will be excessive cation replenishment, making it difficult to further improve the cycle performance, and at the same time reducing the mass energy density of the battery.
[0179] On the other hand, considering that the compound containing the cation-supplementing element will decompose and consume during the cycle, thereby leaving pores in the positive electrode coating, if the cation-supplementing material is added too much in the positive electrode coating, the porosity of the positive electrode coating in the later stage of the cycle will be increased. If the porosity is too high, although the wettability of the positive electrode coating to the electrolyte can be improved, the mechanical strength of the positive electrode coating will decrease, and the positive electrode coating is prone to collapse and rupture. Therefore, considering comprehensively, the mass percentage of the mass of the cation-supplementing material to the total mass of the positive electrode coating ranges from 0.1% to 20%, preferably, from 0.5% to 5%. For example, the mass of the cation-supplementing material not added to the positive electrode coating is defined as m3, and the mass of the cation-supplementing material added to the positive electrode plate is defined as m4, then the mass percentage of the mass of the cation-supplementing material to the total mass of the positive electrode coating is calculated as m4 / (m3+m4)×100%.
[0180] In the above 0.1% to 20%, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 0.1%, 0.5%, 1%, 5%, 10%, 15%, 20%, etc., and the range values between any two of the above point values.
[0181] In the above 0.5% to 5%, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 0.5%, 1%, 2%, 3%, 4%, 5%, etc., and the range values between any two of the above point values.
[0182] In one embodiment, the positive electrode plate includes at least two coating layers, at least one coating layer is disposed on the current collector, and at least another coating layer is disposed on the side of the at least one coating layer away from the current collector. It is defined that the mass percentage of the cation-replenishing material in the at least one coating layer to the mass percentage of the at least one coating layer is W1, and the mass percentage of the cation-replenishing material in the at least another coating layer to the mass percentage of the at least another coating layer is W2, satisfying that W2 is greater than W1.
[0183] It is understandable that in order to facilitate the damage of the coating layer and effectively oxidize and decompose the compound containing the cation-supplementing element inside the coating layer, the coating layer needs to contact the electrolyte. When the cation-supplementing material is added to the positive electrode coating, the probability of contacting the electrolyte is different at different positions of the coating.
[0184] In order to facilitate the contact of cation-supplementing materials with the electrolyte, Figure 2 As shown, the positive electrode plate 100 includes at least two layers of coating, at least one coating 102 is arranged on the current collector 101, and at least another coating 103 is arranged on the side of the at least one coating 102 away from the current collector 101, so that the at least another coating 103 is closer to the surface of the positive electrode coating, increasing the probability of contact with the electrolyte; and it is defined that the mass percentage of the cation-replenishing material in the at least one coating 102 to the mass percentage of the at least one coating 102 is W1, and the mass percentage of the cation-replenishing material in the at least another coating 103 to the mass percentage of the at least another coating 103 is W2, satisfying that W2 is greater than W1, that is, the mass percentage of the cation-replenishing material in the at least two layers of coating is distributed in a concentration gradient; at this time, the mass percentage of the cation-replenishing material in the at least another coating 103 is greater than the mass percentage of the cation-replenishing material in the at least one coating 102, which helps the cation-replenishing material in the at least another coating 103 to contact the electrolyte.
[0185] At the same time, after the cation-replenishing material is decomposed, it helps to improve the porosity of the at least another coating 103. The improvement of the porosity of the at least another coating 103 can further improve the wetting of the positive electrode coating with the electrolyte, so that the electrolyte can penetrate into the at least one coating 102, thereby improving the contact of the cation-replenishing material in the at least one coating 102 with the electrolyte, and improving the decomposition of the cation-replenishing material in the at least one coating 102. In addition, the cation-replenishing material in the at least two layers of coating is distributed in a gradient, which can extend the period of slow release of the cation-replenishing material and improve the battery cycle performance.
[0186] In one embodiment, the positive electrode plate includes a positive electrode material, and the positive electrode material includes one or more of lithium iron phosphate, a ternary layered material, and a spinel positive electrode material.
[0187] The positive electrode plate of the present application includes but is not limited to positive electrode materials, and the positive electrode materials include one or more of lithium iron phosphate, ternary layered materials, and spinel positive electrode materials.
[0188] In one embodiment, the present application also provides a membrane, which includes the cation-supplementing material as described above.
[0189] Optionally, the diaphragm includes a first diaphragm layer and a second diaphragm layer, the second diaphragm layer includes a cation-supplementing material, the diaphragm is arranged on one side of the positive electrode sheet or the negative electrode sheet, and the second diaphragm layer is arranged on the side facing the positive electrode sheet.
[0190] like Figure 3 As shown, a diaphragm 200 of an embodiment of the present application includes a first diaphragm layer 201 and a second diaphragm layer 202. Considering that the decomposition of compounds containing cation-supplementing elements requires a certain decomposition potential, and the potential of the positive electrode is high, which is conducive to decomposition, therefore, the second diaphragm layer 202 including cation-supplementing material is used to face the side of the positive electrode plate.
[0191] In one embodiment, the mass percentage of the cation-compensating material to the mass of the separator is 5% to 200%, preferably, 50% to 80%.
[0192] Considering that if the mass of the cation-replenishing material inside the battery is insufficient, it will be difficult to fully replenish cations in the middle and late stages of the battery cycle. At the same time, if the mass of the cation-replenishing material inside the battery is too much, there will be excessive cation replenishment, making it difficult to further improve the cycle performance, and at the same time, the mass energy density of the battery will be reduced. Comprehensively considered, the mass percentage of the mass of the cation-replenishing material to the mass of the diaphragm is 5% to 200%, preferably 50% to 80%. 。 The mass of the cation-supplementing material not added to the diaphragm is defined as m5, and the mass of the cation-supplementing material added to the diaphragm is defined as m6. The formula for calculating the mass percentage of the cation-supplementing material to the mass of the diaphragm is m6 / m5×100%.
[0193] In the above 5% to 200%, the values include the minimum and maximum values of the range, and every value between such minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 100%, 120%, 140%, 160%, 180%, 200%, etc., and the range values between any two of the above point values.
[0194] In the above 50% to 80%, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 50%, 55%, 60%, 65%, 70%, 75%, 80%, etc., as well as the range values between any two of the above point values.
[0195] In one embodiment, the thickness of the second diaphragm layer is in a range of 50 nm to 50 μm, preferably 2 μm to 5 μm.
[0196] Considering that the diaphragm needs to have a certain degree of air permeability to facilitate ion transmission, and the thickness of the diaphragm cannot be too large to reduce the thickness of the entire battery cell, after the battery cell is installed in the battery cell shell, it helps the battery cell have sufficient expansion space in the battery cell shell.
[0197] That is, if the thickness of the second diaphragm layer is too thick, the air permeability of the entire diaphragm will be reduced, affecting the penetration of the electrolyte into the diaphragm and the migration of ions between the diaphragms. At the same time, if the thickness of the second diaphragm layer is too thick, it will also occupy the volume of the battery cell and reduce the energy density. If the thickness of the second diaphragm layer is too thin, the quality of the cation-supplementing material will be reduced, which is not conducive to the subsequent replenishment of cations in the cycle.
[0198] Based on the above considerations, the thickness of the second diaphragm layer ranges from 50 nm to 50 μm, preferably from 2 μm to 5 μm.
[0199] In the above-mentioned 50nm to 50μm, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 50nm, 80nm, 100nm, 200nm, 500nm, 800nm, 900nm, 1μm, 5μm, 10μm, 15μm, 20μm, 25μm, 30μm, 35μm, 40μm, 45μm, 50μm, etc., and the range value between any two of the above-mentioned point values.
[0200] In the above-mentioned 2μm to 5μm, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 2μm, 3μm, 4μm, 5μm, etc., and the range values between any two of the above-mentioned point values.
[0201] In one embodiment, the material of the diaphragm includes one or more of polyethylene or polypropylene.
[0202] The material of the diaphragm of the present application includes but is not limited to one or more of polyethylene or polypropylene.
[0203] In one embodiment, the present application also provides a method for preparing a cation-supplementing material, comprising: preparing a prepolymer emulsion for a coating layer; adding a compound containing a cation-supplementing element to the prepolymer emulsion for the coating layer, stirring, and heating to obtain the cation-supplementing material.
[0204] like Figure 4 As shown, in order to prepare a cation-supplementing material in which a compound containing a cation-supplementing element is coated in a coating layer, a prepolymer emulsion of the coating layer can be prepared, and the compound containing a cation-supplementing element is added to the prepolymer emulsion of the coating layer, stirred and heated to obtain the cation-supplementing material.
[0205] Prepolymer is a substance formed by preliminary polymerization of monomers.
[0206] Prepolymer emulsion, the state in which the prepolymer is dispersed in water to form an emulsion.
[0207] In order to prepare the cation-supplementing material in which the compound containing the cation-supplementing element is coated in the coating layer, a prepolymer emulsion of the coating layer can be prepared, and the compound containing the cation-supplementing element is added to the prepolymer emulsion of the coating layer, and stirred and heated to obtain the cation-supplementing material. That is, the compound containing the cation-supplementing element is added to the prepolymer emulsion of the coating layer, and the prepolymer is further polymerized on the surface of the compound containing the cation-supplementing element to obtain the compound containing the cation-supplementing element coated in the coating layer.
[0208] In one embodiment, the step of preparing the prepolymer emulsion of the coating layer includes: mixing the constituent monomers of the coating layer with a solvent, and heating the mixture to obtain the prepolymer emulsion of the coating layer.
[0209] In one embodiment, the step of mixing the constituent monomers of the coating layer with a solvent and heating to obtain a prepolymer emulsion of the coating layer includes: mixing the constituent monomers of the coating layer, amino resin monomers, formaldehyde substances, gelatin and water to obtain a mixed solution, adjusting the pH value of the obtained mixed solution to 6.0 to 8.5, heating to 40°C to 70°C, and keeping warm for 20min to 60min to obtain a prepolymer emulsion of the coating layer; wherein the mass of the amino resin monomer is 20% to 70% of the mass of the compound containing the cation-complementing element; the formaldehyde substance is 15% to 120% of the mass of the amino resin monomer; and the gelatin is 3% to 16% of the mass of the amino resin monomer.
[0210] For example, taking gelatin-modified amino resin as a coating layer, amino resin monomer, formaldehyde, gelatin and water are mixed, the pH value of the obtained mixed solution is adjusted to 6.0 to 8.5, heated to 40°C to 70°C, and kept warm for 20min to 60min to obtain a gelatin-modified amino resin prepolymer solution; an appropriate amount of a compound containing a cation-supplementing element is added to the gelatin-modified amino resin prepolymer solution, the temperature is raised to 40°C to 60°C, and the mixture is stirred thoroughly. The mixture is filtered and vacuum dried at 70°C to obtain a cation-supplementing material.
[0211] In one embodiment, the step of adding a compound containing a cation-complementing element to a prepolymer emulsion of a coating layer, stirring and heating to obtain a cation-complementing material includes: adding the compound containing a cation-complementing element to the prepolymer emulsion of the coating layer, stirring, heating to 40° C. to 60° C., filtering, and drying to obtain a cation-complementing material; wherein the mass ratio of the compound containing the cation-complementing element to the prepolymer emulsion of the coating layer is in the range of 20% to 80%.
[0212] The compound containing the cation-complementing element is added to the prepolymer emulsion of the coating layer, and stirred to fully disperse the compound containing the cation-complementing element and the prepolymer emulsion of the coating layer, thereby improving the dispersibility of the compound containing the cation-complementing element and facilitating the preparation of a cation-complementing material of a suitable size. The prepolymer is heated to 40° C. to 60° C. so that a polymerization reaction occurs on the surface of the compound containing the cation-complementing element, and a coating layer is formed on the surface of the compound containing the cation-complementing element to coat the compound containing the cation-complementing element. The cation-complementing material is obtained by filtering and drying.
[0213] In one embodiment, the present application also provides a battery, comprising the cation-supplementing material as described above; or, comprising the electrolyte as described above; or, comprising the positive electrode plate as described above; or, comprising the diaphragm as described above; or, comprising the cation-supplementing material obtained by the preparation method of the cation-supplementing material as described above.
[0214] It can be understood that the battery includes battery cells, battery modules, and battery packs.
[0215] In one embodiment, the present application further provides an electrical device, which includes the battery as described above.
[0216] Since the battery adopts all the technical solutions of all the above embodiments, it has at least all the beneficial effects brought by the technical solutions of the above embodiments, which will not be described one by one here.
[0217] In addition, the battery (battery cell, battery module, battery pack) and the electric device of the present application will be described below with reference to the drawings as appropriate.
[0218] In one embodiment of the present application, a battery cell is provided.
[0219] Typically, a battery cell includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator. During the battery charge and discharge process, active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through. The separator is the separator improved above in this application.
[0220] The positive electrode plate includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector.
[0221] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0222] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0223] In some embodiments, when the secondary battery is a lithium-ion battery, the positive electrode active material may adopt a positive electrode active material for lithium-ion batteries that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
[0224] The battery will be accompanied by Li deintercalation and consumption during the charge and discharge process, and the molar content of Li is different when the battery is discharged to different states. In the list of positive electrode materials in this application, the molar content of Li is the initial state of the material, that is, the state before feeding. The positive electrode material is used in the battery system, and the molar content of Li will change after charge and discharge cycles.
[0225] In the list of positive electrode materials in this application, the molar content of O is only a theoretical value. The release of oxygen from the lattice will cause the molar content of oxygen to change, and the actual molar content of O will fluctuate.
[0226] In some embodiments, the positive electrode film layer may also optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0227] In some embodiments, the positive electrode film layer may further include a conductive agent, for example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0228] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0229] The negative electrode plate includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.
[0230] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0231] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0232] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0233] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0234] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0235] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0236] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0237] The electrolyte plays a role in conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs.
[0238] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0239] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0240] In some embodiments, the electrolyte may further include additives that can improve certain properties of the battery, such as additives that improve the overcharge performance of the battery, additives that improve the high or low temperature performance of the battery, etc.
[0241] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous structure separator with good chemical stability and mechanical stability can be selected.
[0242] In some embodiments, the material of the diaphragm can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The diaphragm can be a single-layer film or a multi-layer composite film, without particular limitation. When the diaphragm is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0243] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0244] In some embodiments, the battery cell may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.
[0245] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0246] The present application has no particular limitation on the shape of the battery cell, which may be cylindrical, square or any other shape. Figure 5 The battery cell 5 is a square structure as an example.
[0247] In some embodiments, reference Figure 6, the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the diaphragm can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0248] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0249] Figure 7 4 is an example of a battery module. Figure 7 In the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.
[0250] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.
[0251] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0252] Figure 8 and Fig. 9 1 is a battery pack 1 as an example. Figure 8 and Fig. 9 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0253] In addition, the present application also provides an electrical device, which includes at least one of the battery cells, battery modules, or battery packs provided in the present application. The battery cells, battery modules, or battery packs can be used as power sources for electrical devices, or as energy storage units for electrical devices. Electrical devices may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0254] As an electrical device, a battery cell, a battery module or a battery pack can be selected according to its usage requirements.
[0255] Fig.10 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the power consumption device's requirements for high power and high energy density of battery cells, a battery pack or a battery module can be used.
[0256] As another example, the device may be a mobile phone, a tablet computer, a notebook computer, etc. The device is usually required to be light and thin, and a battery cell may be used as a power source.
[0257] Example
[0258] Example 1
[0259] Preparation of cation-supplementing materials:
[0260] The amino resin monomer (melamine), formaldehyde substances (37% formaldehyde by mass), gelatin and water are mixed in a mass-to-molar ratio of 36:4:3.6:25, the pH value of the obtained mixed solution is adjusted to 7.5, and the mixture is heated to 60°C for 30 minutes to obtain a gelatin-modified amino resin prepolymer solution;
[0261] A compound containing a cation-supplementing element (potassium oxalate, Dv50 of 50 nm, decomposition potential of 4.7 V) is added to the above-mentioned gelatin-modified amino resin prepolymer solution in a mass ratio of the compound containing a cation-supplementing element to the gelatin-modified amino resin prepolymer solution of 50:50. The temperature is raised to 50°C, stirred thoroughly, filtered, and vacuum dried at 70°C to obtain a cation-supplementing material (the thickness of the coating layer is 50 nm (full coating is adopted), and the Dv50 of the cation-supplementing material is 150 nm).
[0262] Preparation of positive electrode:
[0263] The lithium iron phosphate (LiFePO4) as the positive electrode active material, the cation supplement material, the SuperP as the conductive agent, and the polyvinylidene fluoride (PTFE) as the binder are fully mixed and rolled on the current collector to prepare the pole piece. The mass ratio of LiFePO4, cation supplement material, SuperP, and PTFE in the solid component is 94:1:3:2. The positive electrode slurry is coated on the current collector aluminum foil and dried at 85°C and then cold pressed, and then trimmed and cut, and dried at 85°C under vacuum conditions for 4 hours to make a positive electrode pole piece.
[0264] The mass percentage of the cation-supplementing material to the total mass of the coating is 1% (1÷(94+1+3+2)×100%).
[0265] Preparation of negative electrode sheet:
[0266] The first active material of the negative electrode, graphite, the conductive agent Super P, the binder styrene butadiene rubber (SBR) and the thickener CMC-Na were dispersed in deionized water at a mass ratio of 90:2:3:1.5:1.5 and mixed evenly to obtain a negative electrode slurry. The negative electrode slurry was coated on the negative electrode current collector copper foil and dried at 85°C, then cold pressed, trimmed, cut into pieces, and dried at 120°C under vacuum conditions for 12 hours to make a negative electrode sheet.
[0267] Diaphragm:
[0268] A 16 μm polyethylene film was selected as the base film.
[0269] Preparation of electrolyte:
[0270] The electrolyte was a 1M lithium hexafluorophosphate EC / DMC (1:1 vol%) solution.
[0271] Preparation of the battery:
[0272] The positive electrode sheet, separator, and negative electrode sheet prepared in the above steps are stacked in order, so that the separator is located between the positive and negative electrode sheets to isolate the positive and negative electrodes, and the bare battery cell is wound, and the tabs are welded, and the bare battery cell is placed in an outer package. The electrolyte prepared above is injected into the dried battery cell, and after packaging and standing, it is slowly formed, and then shaped to prepare a lithium-ion battery.
[0273] Example 2 and Example 6
[0274] On the basis of Example 1, the Dv50 of the compound containing the cation-supplementing element in the core material was adjusted to obtain Example 2 and Example 6.
[0275] Example 7 and Example 8
[0276] On the basis of Example 1, the ratio of the mass of the compound containing the cation-complementing element in the core material to the mass of the coating layer was adjusted to obtain Examples 7 and 8.
[0277] Example 9 and Example 10
[0278] On the basis of Example 1, the mass percentage of the compound containing the cation-supplementing element in the core material to the total mass of the positive electrode coating was adjusted to obtain Examples 9 and 10.
[0279] Embodiment 11
[0280] On the basis of Example 1, the material of the coating layer was adjusted to obtain Example 11.
[0281] Example 12 and Example 13
[0282] On the basis of Example 1, the types of compounds containing cation-complementing elements were adjusted to obtain Examples 12 and 13.
[0283] Embodiment 14
[0284] On the basis of Example 1, the cation-supplementing material is not added to the positive electrode coating, but is added to the diaphragm, and a 16 μm polyethylene film is selected as the base film (the first diaphragm layer). The cation-supplementing material containing potassium oxalate and the binder PVDF are uniformly dispersed in nitrogen methyl pyrrolidone (NMP) at a mass ratio of 90:10 to prepare a coating slurry. The slurry is uniformly coated on one side of the PE base film (the first diaphragm layer), and dried at 60°C in vacuum to obtain a cation-supplementing coating (the second diaphragm layer) with a coating thickness of 2 μm, and the mass of the cation-supplementing material accounts for 5% of the mass of the diaphragm.
[0285] Example 15 and Example 16
[0286] On the basis of Example 14, the mass of the cation-supplementing material added to the separator and the thickness of the coating were adjusted to obtain Examples 15 and 16.
[0287] Example 17 to Example 19
[0288] On the basis of Example 1, a cation-supplementing material is added to the electrolyte to obtain Examples 17 to 19.
[0289] Comparative Example 1
[0290] On the basis of Example 1, a 16 μm polyethylene film was selected as the base film. Potassium oxalate and PVDF were uniformly dispersed in nitrogen methyl pyrrolidone (NMP) at a mass ratio of 90:10 to prepare a coating slurry. The slurry was uniformly coated on one side of the PE separator and dried at 60°C in vacuum to obtain a cation-replenishing coating with a coating thickness of 4 μm. Potassium oxalate that was not coated by the coating layer was added to the separator.
[0291] Comparative Example 2
[0292] On the basis of Example 1, no cation-supplementing material is added to the positive electrode coating, so that no cation-supplementing material is added to the entire battery.
[0293] Performance Testing
[0294] Electrochemical performance test: The above lithium-ion battery was cycled using a 0.5C / 0.5C constant current charge and discharge method with a voltage range of 2.5-3.65 V. During the cycle, the battery was charged with high voltage cation supplementation every 50 cycles, specifically by charging to 4.3 V at a 0.1C constant current, and then tested according to normal cycle charge and discharge.
[0295] To maintain consistency, the comparative examples were also tested in the same manner as above.
[0296] Table 1 List of Examples
[0297]
[0298]
[0299]
[0300] It can be seen from the test results in Table 1 that compared with the comparative example, the embodiment adds a cation-supplementing material, and the cation-supplementing material includes a core material (a compound containing a cation-supplementing element) and a coating layer that completely covers the surface of the core material. It can be seen that after the battery in the embodiment is cycled 400 times, its capacity retention performance is improved, indicating that the cation-supplementing material of the present application can improve the cycle performance of the battery.
[0301] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. All equivalent structural changes made using the contents of the present invention's specification and drawings, or directly / indirectly applied in other related technical fields, are included in the patent protection scope of the present invention.
Claims
1. A cation supplement material, characterized in that: The invention comprises a core material and a coating layer arranged on the surface of the core material, wherein the core material comprises a compound containing a cation-supplementing element.
2. The cation-supplementing material according to claim 1, characterized in that The cation-supplementing material is applied to lithium-ion batteries, and the compound containing cation-supplementing elements includes non-lithium element compounds.
3. The cation-supplementing material according to claim 1 or 2, characterized in that: The decomposition potential of the compound containing the cation-supplementing element is 2V to 5V, preferably, 3V to 5V.
4. The cation-supplementing material according to any one of claims 1 to 3, characterized in that The compound containing the cation-supplementing element includes at least one of a Group IA element compound and a Group IA element compound.
5. The cation-supplementing material according to claim 4, characterized in that The Group IA element compound includes at least one of an oxide of a Group IA element, a peroxide of a Group IA element, and an oxalate of a Group IA element; And / or, the Group IIA element compound includes at least one of an oxide of a Group IIA element, a peroxide of a Group IIA element, and an oxalate of a Group IIA element.
6. The cation-supplementing material according to any one of claims 1 to 5, characterized in that The compound containing the cationic supplementing element includes at least one of sodium oxide, sodium peroxide, sodium oxalate, potassium oxide, potassium peroxide, potassium oxalate, magnesium oxide, magnesium peroxide, magnesium oxalate, calcium oxide, calcium peroxide, calcium oxalate, strontium oxide, strontium peroxide and strontium oxalate.
7. The cation-supplementing material according to any one of claims 1 to 6, characterized in that The Dv50 value of the cation-supplementing material ranges from 50 nm to 150 μm, preferably, from 50 nm to 10 μm.
8. The cation-supplementing material according to any one of claims 1 to 7, characterized in that The Dv50 value of the compound containing a cation-complementing element is in the range of 20 nm to 100 μm, preferably, 50 nm to 2 μm.
9. The cation-supplementing material according to any one of claims 1 to 8, characterized in that The ratio of the mass of the compound containing the cation-complementing element to the mass of the coating layer ranges from 1:99 to 99:1, preferably, from 50:50 to 80:
20.
10. The cation-supplementing material according to any one of claims 1 to 9, characterized in that The coating layer has a thickness ranging from 50 nm to 3 μm, preferably, from 100 nm to 500 nm.
11. The cation-supplementing material according to any one of claims 1 to 10, characterized in that The material of the coating layer includes at least one of gelatin-modified amino resin, polyurea resin and polyvinyl chloride.
12. The cation-supplementing material according to any one of claims 1 to 11, characterized in that The coating layer completely covers the surface of the core material.
13. An electrolyte, characterized in that: The electrolyte comprises the cation-supplementing material according to any one of claims 1 to 12.
14. The electrolyte according to claim 13, wherein the mass percentage of the cation-supplementing material to the total mass of the electrolyte is in the range of 5% to 20%, preferably, 10% to 12%.
15. A positive electrode sheet, characterized in that: The positive electrode sheet comprises the cation-supplementing material according to any one of claims 1 to 12.
16. The positive electrode sheet according to claim 15, characterized in that: The positive electrode plate includes a current collector and a positive electrode coating disposed on the current collector, and the mass percentage of the cation-supplementing material to the total mass of the positive electrode coating ranges from 0.1% to 20%, preferably, from 0.5% to 5%.
17. The positive electrode sheet according to claim 16, characterized in that: The positive electrode plate includes at least two layers of coating, at least one of the coatings is arranged on the current collector, and at least another coating is arranged on the side of at least one of the coatings away from the current collector. It is defined that the mass percentage of the cation-replenishing material in at least one of the coatings is W1, and the mass percentage of the cation-replenishing material in at least another of the coatings is W2, satisfying that W2 is greater than W1.
18. The positive electrode sheet according to any one of claims 15 to 17, characterized in that: The positive electrode plate includes a positive electrode material, and the positive electrode material includes one or more of lithium iron phosphate, ternary layered materials, and spinel positive electrode materials.
19. A diaphragm, characterized in that: The separator comprises the cation-supplementing material according to any one of claims 1 to 12.
20. The diaphragm according to claim 19, characterized in that The diaphragm includes a first diaphragm layer and a second diaphragm layer, the second diaphragm layer includes the cation-supplementing material, the diaphragm is arranged on one side of the positive electrode sheet or the negative electrode sheet, and the second diaphragm layer is facing the side of the positive electrode sheet.
21. The diaphragm according to claim 19 or 20, characterized in that The mass percentage of the cation-supplementing material to the mass of the separator is 5% to 200%, preferably 50% to 80%.
22. The diaphragm according to claim 21, characterized in that The thickness of the second diaphragm layer is in the range of 50 nm to 50 μm, preferably, in the range of 2 μm to 5 μm.
23. The diaphragm according to any one of claims 19 to 22, characterized in that The material of the diaphragm includes one or more of polyethylene or polypropylene.
24. A method for preparing a cation-supplementing material according to any one of claims 1 to 12, characterized in that: include: preparing a prepolymer emulsion for a coating layer; The compound containing the cation-compensating element is added into the prepolymer emulsion of the coating layer, stirred and heated to obtain the cation-compensating material.
25. The method for preparing a cation-supplementing material according to claim 24, characterized in that: The step of preparing the prepolymer emulsion of the coating layer comprises: mixing the constituent monomers of the coating layer with a solvent, and heating the mixture to obtain the prepolymer emulsion of the coating layer.
26. The method for preparing a cation-supplementing material according to claim 25, characterized in that: The step of mixing the monomers constituting the coating layer with a solvent and heating to obtain a prepolymer emulsion of the coating layer comprises: mixing the monomers constituting the coating layer, amino resin monomers, formaldehyde substances, gelatin and water to obtain a mixed solution, adjusting the pH value of the obtained mixed solution to 6.0 to 8.5, heating to 40° C. to 70° C., and keeping the temperature for 20 min to 60 min to obtain a prepolymer emulsion of the coating layer; The mass of the amino resin monomer is 20% to 70% of the mass of the compound containing the cation-supplementing element; the formaldehyde substance is 15% to 120% of the mass of the amino resin monomer; and the gelatin is 3% to 16% of the mass of the amino resin monomer.
27. The method for preparing a cation-supplementing material according to any one of claims 24 to 26, characterized in that: The step of adding a compound containing a cation-supplementing element to the prepolymer emulsion of the coating layer, stirring and heating to obtain a cation-supplementing material comprises: Adding a compound containing a cation-supplementing element into the prepolymer emulsion of the coating layer, stirring, heating to 40° C. to 60° C., filtering, and drying to obtain a cation-supplementing material; Wherein, the mass ratio of the compound of the cation-supplementing element to the prepolymer emulsion of the coating layer ranges from 20% to 80%.
28. A battery, characterized in that: The battery comprises a cation-supplementing material as claimed in any one of claims 1 to 12; Or, comprising the electrolyte as claimed in claim 13 or 14; Or, comprising a positive electrode sheet as claimed in any one of claims 15 to 18; Or, comprising a diaphragm as claimed in any one of claims 19 to 23; Alternatively, the cation-supplementing material comprises a cation-supplementing material obtained by the method for preparing the cation-supplementing material according to any one of claims 24 to 27.
29. An electrical device, characterized in that: The electrical device comprises the battery as claimed in claim 28.